Mengukur Loyalitas Merek Fashion Muslim berdasarkan Aktivitas Pemasaran Media Sosial dan Ekuitas Merek - Pavita Auliahasna Oktadhivia (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to examine the application of the commando teaching The development fashion in Indonesia is increasing following the times. With ever-increasing technology, we can easily access social media like Facebook, Instagram, Twitter, or Website about muslim fashion trends. Due to the increasingly advanced development of fashion muslim, connoisseurs fashion will look for the best fashion muslim of her/his version. This study aims to determine the influence felt by consumers in marketing on social media regarding loyalty on that fashion muslim. This research uses SEM (Stuctual Equation Modeling) with the help of AMOS (Analysis of Moment Structures) software, with 201 respondents. The results of this study indicate that there is a positive influence of social media marketing activities on brand experience, social media benefits, consumer-based brand equity, and brand loyalty. Through experience the brand brings cognitive benefits, social integrative, personal integrative, and hedonic benefits directs a significant relationship to consumer-based brand equity which gives the effect of brand loyalty to consumers. That is, the existence of social media marketing activities can have a positive impact by increasing consumer brand loyalty to the fashion muslim.